(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Headache may occur due to different pathological condition in eye, brain or nasal cavity. Objective: The purpose of the study was to evaluate the pattern of headache patients in Eye OPD. Methodology: This retrospective study was carried out in the OPD of eye in the Sadar Hospital of Moulvibazar district of Bangladesh which was conducted from October 2014 to April 2015 for a period of seven (7) months. Here data of headache patients were collected from hospital record book with patterns of headache. Then total data were tabulated on age, sex, pattern of headache and chief complains. Result: The total study showed that out of 2206 patients 308(13.96%) patient came in Eye OPD. Among the headache patients, female were more (65%). Headache patients were more in 11 to 20 years (37.66%) age group and then 21 to 30 years (21.1%). However patients were less below 10 years (7.46%) with male and female nearly equal numbers. Above 10 years, female patients are more than male. In this study, we found migraine headache (69%) which included both purely migraine headache and mixed type headache comprising both migraine and tension, to be much more than non migraine headache (31%). Besides most headache patients (45.12%) complains of not only of headache also of dimness of vision, redness of eye, watering, nausea and vomiting. Conclusion: This study shows that a significant number of patients are suffering from headache. Its prevalence is more among female and young age group. Journal of National Institute of Neurosciences Bangladesh, 2016;2(2): 75-78